Penerapan Model Project Based Learning Melalui Herbarium Book Materi Pterydophyta Terhadap Kreativitas Peserta Didik Kelas X SMA Karya Sekadau - Iluminata Trifonia; Eka Trisianawati; Herditiya (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2024)
Learning models are techniques used to facilitate children in understanding the material delivered by the instructor. The learning model provided by the teacher to students ensures that their understanding aligns with the material and theme selected. This study aims to measure students' creativity and to determine significant differences in creativity levels between the experimental and control classes before and after applying the Project-Based Learning model and the Guided Discovery Learning model. This research employs an experimental method in the form of a quasi-experimental design. The design used is the nonequivalent control group design, which involves comparing subjects in the control group and the experimental group through pre-tests and post-tests. The results of the study show that students' creativity in the experimental class had an average pre-test score of 53.97, an average post-test score of 84.82, and an N-Gain result of 0.65, categorized as moderate. In the control class, students' creativity had an average pre-test score of 51.63, an average post-test score of 76.06, and an N-Gain result of 0.45, also categorized as moderate. There was a significant difference in students' creativity levels after learning with the Project-Based Learning model using a herbarium book on Pteridophyta material compared to the control group using the Guided Discovery Learning model through plant observation, with a 2-tailed significance value of 0.000 ? 0.005. Therefore, the alternative hypothesis is accepted.